Propuesta de un sistema de costos por órdenes de producción en un taller de diseño y confección de prendas de vestir - Bolaños Maya, Nicole Andrea; Castillo Ochoa, Juan Sebastian (Universidad Antonio Nariño, 2023)
Since the processes of globalization entered the planet, organizations have been interconnecting in a more immediate way, which has led to a coherent look at the performance of resources, since not only do they compete with national organizations, but also with foreign organizations, which demand to examine the market, to maneuver production prices and thus also ask for tactics in making managerial elections.